POLITIK HUKUM PEMBENTUKAN UNDANG-UNDANGLARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - wafiya, wafiya (FIAT JUSTISIA, 2014)
This research aims to outline the policy choice of law in forming the Law on prohibition of monopoly and business competition. Based on the normative approach and by using secondary data, it can be concluded that prior to Act Number 5 of 1999 established, practices of monopoly and business competition are not regulated within the law, after the birth of that Law, business activity is prohibited if it proves detrimental to other businesses, consumers, society and the State. Businessperson that practicing monopoly and unfair business competition among another businessperson obviously threatened by administrative and criminal sanctions. Choice of law is made to anticipate the free market in the era of economic globalization in order to realize the prosperity and welfare of the people as mandated by the 1945 Constitution. Law enforcement of business competition in Indonesia submitted to the supervisor commission of business competition (KPPU), in addition to the involvement of police officers, prosecutors, and courts. Enforcement of competition law violations must be made in advance by the Commission.Â Keywords: Legal Politic, Prohibition of Monopoly and Unfair Business Competition.